Analysis of the Role of Airport Operation Landside and Terminal Units in Handling Earthquake and Tsunami Emergency Situations at Yogyakarta International Airport - Hidayatullah, Rahmat; Widagdo, Djoko (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
The Airport Operation Landside and Terminal unit is one of the service units at Yogyakarta International Airport, the Airport Operation Landside and Terminal unit has the task of supervising operational activities from the air side and land side covering all arrival and departure activities and checking service facilities for service users and providing all forms of information at Yogyakarta International Airport. The Airport Operation Landside and Terminal Unit took part in handling the earthquake and tsunami emergency at Yogyakarta International Airport, this was based on the work instructions (IK) made by PT. Angkasa Pura 1 to provide temporary assistance to users of Yogyakarta international airport services, both by providing information services regarding the occurrence of earthquakes and tsunamis, directing evacuation routes, and providing peace of mind to airport service users so that they feel safe, these officers are usually called Floors. Warden. This research uses qualitative research methods using data collection techniques including observation by conducting observations in the airport area, interviews with 3 sources including the Airport Operation Landside and Terminal Manager (YIA.OL), Passenger Service Supervisor (PSS) and Terminal Service Officer (TSO) and documentation using data analysis techniques in the form of data collection, data reduction, data presentation, and drawing conclusions. The research results showed that airport operation landside and terminal officers at the time of the earthquake and tsunami emergency carried out their duties by referring to Work Instructions (IK), had been provided with education and simulations about handling emergencies, emergency support facilities were available, but still There are obstacles in the process of handling emergencies, such as a lack of floor wardens, minimal safety tools available, and damage to service operational support facilities due to the aftermath of the earthquake. Despite the obstacles that occur, floor warden officers continue to carry out their responsibilities to the maximum in order to create safety for all users of Yogyakarta international airport services.